Characterising the electrothermal properties of microstrip-coupled TES detectors. - art. no. 627507 - Dunlop, L; Glowacka, D; Goldie, D; Withington, S; Yassin, G (2006)
Microstrip-coupled Transition Edge Sensors (TESs) are important because they can be combined with waveguide-horn technology to produce sensitive bolometric detectors with well-defined, single-mode beam patterns and polarisation characteristics. They also allow superconducting RF filters to be included on the detector chips. Our own design of TES uses a finline taper to transform between waveguide and superconducting Nb microstrip. The microstrip transports the signal to a matched Au-Cu resistor, which is deposited on a thermally isolated SiN membrane. The dissipated RF power causes the resistance of a Mo-Cu TES bilayer to increase, and the resulting reduction in bias current is read out by a SQUID. We have fabricated TES bilayers with critical temperatures of 400 to 600mK, and deduced dark NEPs as low as 3 x 10(-17)W/root Hz at 150GHz. In this paper we describe a number of experiments that were carried out in order to investigate the electrothermal behaviour of microstrip-coupled TESs. We show that the electrothermal behaviour of microstrip-coupled TESs can be as good as that of free-space TESs, and therefore that they are suitable for high-performance astronomical applications.